The Hera Saturn entry probe mission. (1st October 2016) - Mousis, O.; Atkinson, D.H.; Spilker, T.; Venkatapathy, E.; Poncy, J.; Frampton, R.; Coustenis, A.; Reh, K.; Lebreton, J.-P.; Fletcher, L.N.; Hueso, R.; Amato, M.J.; et al.
Abstract: The Hera Saturn entry probe mission is proposed as an M-class mission led by ESA with a contribution from NASA. It consists of one atmospheric probe to be sent into the atmosphere of Saturn, and a Carrier-Relay spacecraft. In this concept, the Hera probe is composed of ESA and NASA elements, and the Carrier-Relay Spacecraft is delivered by ESA. The probe is powered by batteries, and the Carrier-Relay Spacecraft is powered by solar panels and batteries. We anticipate two major subsystems to be supplied by the United States, either by direct procurement by ESA or by contribution from NASA: the solar electric power system (including solar arrays and the power management and distribution system), and the probe entry system (including the thermal protection shield and aeroshell). Hera is designed to perform in situ measurements of the chemical and isotopic compositions as well as the dynamics of Saturn's atmosphere using a single probe, with the goal of improving our understanding of the origin, formation, and evolution of Saturn, the giant planets and their satellite systems, with extrapolation to extrasolar planets. Hera 's aim is to probe well into the cloud-forming region of the troposphere, below the region accessible to remote sensing, to the locations where certain cosmogenically abundant species are expected to be well mixed. By leading to an improved understanding of the processes by which giant planets formed, including the composition and properties of the local solar nebula at the time and location of giant planet formation, Hera will extend the legacy of the Galileo and Cassini missions by further addressing the creation, formation, and chemical, dynamical, and thermal evolution of the giant planets, the entire solar system including Earth and the other terrestrial planets, and formation of other planetary systems.